Quicklime-stabilized Tuff and Clayey Soils for Highway A3 Construction in Northern Tunisia - Ghazouani, Nejib (Engineering, Technology & Applied Science Research, 2024)
This study presents a comprehensive examination of the effects of quicklime (QL) addition on the stabilization of two distinct clayey soils with high (CH) and low plasticity (CL-tuff). The results showed that incorporating QL into the soils substantially improves their stabilization characteristics. Specifically, the addition of QL results in a notable decrease in the final water content of both soils, as shown by a reduction from 23.04 to 19.06% in CH and from 18.07 to 17.1% in CL-tuff at 4% QL addition. Furthermore, this study reveals a transformation in the plasticity properties of soils. Liquid Limit (LL) and Plasticity Index (PI) were reduced, with CH-tuff exhibiting a significant decrease in PI from 48 to 12 and an increase in Plastic Limit (PL) from 21.8 to 55 at 4% QL. CL-tuff also showed reduced plasticity, with PI decreasing to 8.33 at 4% QL. Additionally, the Immediate Bearing Index (IBI) was improved for both soil samples, indicating improved load-bearing capacities. For CH samples, IBI improved from 6.37 to 11.99 at 4% QL addition, while for CL-tuff, it increased dramatically from 4.5 to 23.6 for the same QL percentage. The findings underscore the effectiveness of QL in improving soil properties crucial for chemical stabilization, providing evidence that QL addition can be a key technique in soil stabilization, especially for soils with high plasticity or those requiring increased bearing strength.